Associative Meanings in Semantic Prototypicality of Durian Naming in Jember, East Java, Indonesia - Sukarno Sukarno; Hairus Salikin; Wisasongko Wisasongko; Indah Wahyuningsih; Agung Tri Wahyuningsih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research aims at revealing the associative meanings of durian naming on the subordinate level. The data of this research are durian names taken from two biggest places producing large number of durian harvesting in Jember, East Java. Employing Leech’s classification of meanings, durian as the semantical prototype is broken down into variously associative meanings. Based on the properties that a durian has, the specialties or distinctive marks come to be the characteristics that are associated to the names given. The result shows that among 30 durian names, they are distributed into 4 associative meanings comprising connotative meaning (19 names), affective meaning (6 names), reflected meaning (3 names), and social meaning (2 names). Those groupings of meanings as the subordinate levels of semantical prototype of durian come to exists due to the associatively mental image or concept of experience proximity.